2022
DOI: 10.1073/pnas.2218630120
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of LGR ligand α2/β5 from Caenorhabditis elegans with implications for the evolution of glycoprotein hormones

Abstract: A family of leucine-rich-repeat-containing G-protein-coupled receptors (LGRs) mediate diverse physiological responses when complexed with their cognate ligands. LGRs are present in all metazoan animals. In humans, the LGR ligands include glycoprotein hormones (GPHs) chorionic gonadotropin (hCG), luteinizing hormone, follicle-stimulating hormone (hFSH), and thyroid-stimulating hormone (hTSH). These hormones are αβ heterodimers of cystine-knot protein chains. LGRs and their ligand chains have coevolved. Ancestra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 72 publications
2
7
0
Order By: Relevance
“…Phylogenetic analyses also revealed orthologs of the thyrostimulin GPA2 and GPB5 subunits in the C. elegans genome ( 9 , 15 , 21 , 40 ), which carry a cysteine knot motif of six cysteine residues that is typical of glycoprotein hormone subunits ( 44 , 45 ). Recent analysis of the crystal structure of C. elegans GPA2/GPB5 validates its structural similarity to vertebrate glycoprotein hormones that was previously found by comparative genomic analyses ( 3 , 8 , 46 ). In addition, C. elegans has only one receptor ortholog of the vertebrate glycoprotein hormone receptors.…”
Section: Introductionsupporting
confidence: 75%
“…Phylogenetic analyses also revealed orthologs of the thyrostimulin GPA2 and GPB5 subunits in the C. elegans genome ( 9 , 15 , 21 , 40 ), which carry a cysteine knot motif of six cysteine residues that is typical of glycoprotein hormone subunits ( 44 , 45 ). Recent analysis of the crystal structure of C. elegans GPA2/GPB5 validates its structural similarity to vertebrate glycoprotein hormones that was previously found by comparative genomic analyses ( 3 , 8 , 46 ). In addition, C. elegans has only one receptor ortholog of the vertebrate glycoprotein hormone receptors.…”
Section: Introductionsupporting
confidence: 75%
“…Heterodimerization of GPLA-1 and GPLB-1 might thus not be essential for activating the receptor. This is in line with crystal structure analysis, which demonstrates high similarity between C. elegans GPLA-1 and GPLB-1, suggesting that thyrostimulin-like subunits might have evolved from a monomeric or homodimeric ancestral hormone ( Gong et al, 2023 ). Several theories on the evolutionary origin of glycoprotein hormone subunits have previously suggested that the ancestral thyrostimulin subunits arose in early metazoans from a single mono- or homodimeric antecedent that contained an α- or β-like structure ( Gong et al, 2023 ; Park et al, 2005 ; Roch and Sherwood, 2014 ).…”
Section: Evolutionary Conservation Of Glycoprotein Hormone-like Signa...supporting
confidence: 85%
“…In many of the reported FSHR-1 functions, details concerning its interaction partner(s) are lacking because ligands of FSHR-1 were identified only recently ( Kenis et al, 2023 ). Like other invertebrates, C. elegans has single orthologs of GPA2 and GPB5, named glycoprotein hormone-like alpha 1 (GPLA-1) and -beta 1 (GPLB-1) ( Gong et al, 2023 ; Hsu et al, 2002 ; Kenis et al, 2023 ; Oishi et al, 2009 ). GPLA-1/GPLB-1 act as cognate ligands of FSHR-1 in vivo and activate FSHR-1 in cultured cells, stimulating cAMP signaling ( Kenis et al, 2023 ; Kudo et al, 2000 ; Wang et al, 2023 ).…”
Section: Evolutionary Conservation Of Glycoprotein Hormone-like Signa...mentioning
confidence: 99%
“…Phylogenetic analyses show a clear conservation of thyrostimulin GPA2 and GPB5 polypeptides across Protostomia and Deuterostomia, but their physiological roles remain elusive [7][8][9]14,26,29,46 . In invertebrates, GPA2/GPB5 orthologs have only been functionally characterized in arthropods 12,[38][39][40] .…”
Section: Discussionmentioning
confidence: 99%
“…Here, we show that C. elegans FSHR-1 is activated by GPLA-1/GPLB-1 as well as individual GPLA-1 and GPLB-1 polypeptides. Recent analyses of the crystal structure of GPLA-1/GPLB-1 revealed that the two subunits indeed heterodimerize but are also more symmetric in structure as compared to the alpha and beta subunits of human CG and FSH 46 . Our results are in line with this study.…”
Section: Discussionmentioning
confidence: 99%